Pharmacokinetics and pharmacodynamics of sublingual sufentanil for postoperative pain management. (8th December 2017) - van de Donk, T.; Ward, S.; Langford, R.; Dahan, A.
Summary: Achieving successful treatment of postoperative pain remains a challenge. Recently, a sufentanil sublingual tablet system has been developed for treatment of moderate‐to‐severe postoperative pain. The phenylpiperidine sufentanil is a potent analgesic that rapidly crosses the blood–brain barrier and selectively activates central μ‐opioid receptors. The system makes use of a hand‐held dispenser system, which contains forty 15‐μg sufentanil sublingual micro‐tablets. The patient can release one tablet at 20‐min intervals using a unique radiofrequency adhesive tag, which is wrapped around the patient's thumb. In this review, the authors discuss the pharmacology of sublingual sufentanil with reference to its suitability in the treatment of postoperative pain, the current evidence for the sublingual sufentanil system in postoperative pain treatment, and advantages and limitations of the sublingual system. We conclude that sufentanil is suited for the transmucosal route due to its pharmacokinetic profile, including rapid onset, absence of active metabolites and low tissue accumulation. The efficacy and safety of the sufentanil sublingual tablet system has been shown in over 600 patients in a limited set of studies; further independent studies are required to determine the position of the system among other forms of postoperative pain treatment. We conclude that the sublingual sufentanil tablet system allows effective pain relief, and allows patients to control their own pain relief and early postoperative mobility.